Instagrammable Culture: Implications of Social Media on the Younger Generation's Perception of Cultural Art - Shofiyyah, Nilna Azizatus; Amini, Hielda; Nurhasanah, Lilis Romdon; Kurganov Maksim Vladimirovich (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
This research investigates the impact of social media, specifically Instagram, on shaping the perceptions of the younger generation towards cultural art. Employing qualitative research methods and conducting a comprehensive literature analysis, the study explores the phenomenon termed Instagrammable Culture. The primary focus is to comprehend how this cultural shift influences the younger generation in understanding, appreciating, and promoting cultural art forms. The research also seeks to identify alterations in the aesthetics of cultural art, the commercialization it undergoes due to social media prevalence, and shifts in direct experiences associated with cultural art. The overarching goal is to provide valuable insights for researchers, art practitioners, and educators, contributing to the preservation of the integrity of cultural art. In conclusion, this research advocates for more profound and meaningful engagements with cultural art in the rapidly advancing digital era to ensure its continued relevance and significance.